- 1-800-665-6601
- [email protected]

Let’s take an algebraic equation to show the steps to solve for y.

**Example 1**: - Solve the equation 2 y + 9 = 10 for y.

**Solution**: - 2 y + 9 = 10 … (1)

Instruction |
Solution |

· Try to free the L.H.S. from the constant.So subtract 9 to both sides of the equation (1). |
(2y + 9) – 9 = 10 – 9 2 y = 1 … (2) |

· Remove the coefficient of y.Therefore divide both sides by two of equation (2) |
2 y / 2 = 1 /2 y = 1 / 2 |

Therefore y = ½

Instruction | Solution |

· Try to free the L.H.S. from the constant.So subtract 2 to both sides of the equation (1) |
(4 y + 2) – 2 = (6 y – 3) – 2 Or, 4 y + 2 – 2 = 6 y – 3 – 2 Or, 4 y = 6 y – 5 … (2) |

· Try to free the R.H.S. from the variable i.e., y.Therefore subtract 6y to both sides of the equation. |
4 y – 6y = (6 y – 5) – 6y -2 y = - 5 … (3) |

· Remove the coefficient of y.Therefore divide both sides by - 2 of equation (3) |
-2y / - 2 = - 5 / - 2 y = 5 / 2 |

Therefore y = 5/2